A decisão ecológico-jurídica sob a perspectiva sistêmica - Trombini, Gabrielle (My University, 2014)
The present dissertation observes the legal decision referring to ecological questions, especially in what it concerns to the possibility of achieving an effective environmental protection through the decisions issued by the Judiciary. Through the Niklas Luhmann´s Theory of Autopoietic Systems, the decision is examined as communication of the legal system, which is a functionally differentiated system delimited by the Legal/Illegal code. Because of being considered a guide of behavior, the legal system works with the function of stabilizing expectations, and in this context appears the dogmatic element of res judicata, which aims to bring security and certainty to the society. However, as it is elucidated in the present study, in the contemporaneousness the ideals of security and certainty are obscured by the new social reality, which highlights risks and indeterminations deriving from the complex society. In this way, appear the so-called ecological risks, which are the consequence of decisions derived especially from the organizations, such as the Judiciary. Thus, it is observed and questioned how can the legal system, through its deciding programs, perform effectively the ecological protection idealized by the 1988´s Brazilian Federal Constitution. To answer such question, it is examined the proposal to offer differentiated treatment to the res judicata, so that the legal decisions take into account the imminent risk encrusted in the contemporary society. It is questioned about the possibility of allowing the mitigation of res judicata´s effects in ecological legal questions, analyzing possible consequences of this decision.
A presente dissertação observa a decisão judicial referente a questões ecológicas, especialmente no que concerne à possibilidade de alcançar uma efetiva proteção ecológica através das decisões emanadas do Poder Judiciário. Por meio da Teoria dos Sistemas Autopoiéticos de Niklas Luhmann, se examina a decisão como comunicação do sistema jurídico, sendo este um sistema funcionalmente diferenciado delimitado pelo código Direito/Não Direito. Por ser considerado um guia de comportamento, o sistema jurídico atua com a função de estabilizar expectativas, e neste contexto aparece o elemento dogmático da coisa julgada, que busca trazer segurança e certeza para a sociedade. Porém, como se elucida no presente estudo, na contemporaneidade os ideais de segurança e certeza são ofuscados pela nova realidade social, que evidencia riscos e indeterminações advindos da sociedade complexa. Desta forma, aparecem os chamados riscos ecológicos, que são consequência das decisões oriundas especialmente das organizações, como é o caso do Poder Judiciário. Sendo assim, se observa e questiona de que forma pode o sistema jurídico, através de seus programas decisionais, realizar efetivamente a proteção ecológica idealizada pela Constituição Federal brasileira, de 1988. Para responder a tal pergunta, examina-se a proposta de oferecer tratamento diferenciado à coisa julgada, de modo que as decisões judiciais levem em consideração o iminente risco incrustado na sociedade contemporânea. Questiona-se a possibilidade de permitir a mitigação dos efeitos da coisa julgada em questões jurídicas ecológicas, analisando possíveis consequências desta decisão.
Keywords: Direito; Decisão judicial; Teoria dos sistemas autopoiéticos; Risco ecológico; Coisa julgada; Legal decision; Autopoietic systems theory; Ecological risk; Res judicata